SINTESIS NANOKITOSAN DARI LIMBAH CANGKANG HALILING (Filopaludina javanica) KALIMANTAN SELATAN - Siska Musiam; Noor Aisyah (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Haliling (Filopaludina javanica) is usually consumed as a side dish by the people of South Kalimantan by taking part of the meat, then the shell is disposed as untapped waste. This research utilizes the waste from the haliling shell as raw material for chitosan synthesis. Chitosan is a multipurpose natural polymer used in the biomedical field as a protective active drug. Haliling shell powder deproteinated with a solution NaOH 4%(w/v) of 10:1 ratio by refluxing for 2 hours at 100°C. The results of the deproteination reaction were demineralized with a solution of HCl 1 N of 15:1 ratio which was stirred for 2 hours at room temperature. Furthermore, the demineralization reaction results are depigmented with a solution of NaOCl 0.315%(w/v) of 10:1 ratio which was stirred for 2 hours at 40°C to obtain chitin. Deacetylation reaction was carried out on chitin using a solution of NaOH 60%(w/v) of 20:1 ratio by refluxing it for 2 hours at 80°C so that chitosan was obtained. Chitosan nanoparticles were synthesized using the ionic gelation method with sodium tripolyphosphate crosslinker. The product obtained is known as chitosan based on the results of FTIR analysis which shows the emergence of the -NH2 amine group at wave number 3300-3500 cm-1 with an average size of chitosan nanoparticles of 500 nm.